The Modernity and Legal Unification of the Portuguese-Spanish-Ibero-American Legal Culture in the 19th and 20th Centuries - Visegrády, Antal; Aparicio, Zoltán Gergely (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2024)
The topic of legal culture[1] is much broader and more comprehensive than its richness of thought could be perceived in the context of an article. Connecting law to the concept of culture is a relatively recent phenomenon. The concept of culture dating from the middle of the 19th century and still accepted today is that culture means everything that has been created through the physical and mental work of human society. At the beginning of the 20th century, German jurist Kohler regarded contribution to the advancement of culture as the most important task of law and jurisprudence. For him, law is a creative science which evolves to satisfy the needs of society. Professor Radbruch from Germany defined law as a cultural power, a component of culture. Zjelmann saw the main value of comparing laws in that it allows law to be perceived as a cultural phenomenon.